Vplyv kalciových antagonistov na celkový obsah vápnika a horcíka v aorte králikov po podávaní cholesterolovej diéty - Drábková, E; Lazarová, Z; Edelsteinová, S; Czirfusz, A; Gratzlová, J; Holub, P (Casopis lekaru ceskych, 1992)
The objective of the work was to investigate the effect of calcium blockers--dilthiazem (2 mg.kg-1.day-1), isradipine (2.5 mg.kg-1.day-1) and verapamil (0.25 mg.kg-1.day-1) on the calcium and magnesium content of the rabbit aorta with experimental atherosclerosis induced by a 1% cholesterol diet. In the aorta of rabbits kept on a cholesterol diet the calcium and magnesium content, as compared with a control group on a ordinary diet, increased significantly. In the experimental groups to whom during the eight-week period on the cholesterol diet at regular 12-hour intervals calcium antagonists were administered the calcium and magnesium content of the aorta reached normal levels. The antiatherogenic effect was, however, produced only by verapamil when administered in therapeutic doses.
Keywords: cholesterol dietní; blokátory kalciových kanálů; vápník; hořčík; Calcium; mužské pohlaví; aorta; arterioskleróza; Arteriosclerosis; zvířata; Calcium Channel Blockers; králíci; Rabbits; Magnesium; Aorta; Male; Cholesterol, Dietary; Animals